Menelusuri Karakter Historis-Teologis Aliran Pentakostal Mengenai Pneumatologi Dalam Kitab Kisah Para Rasul - Stevanus, Kalis (Jurnal Amanat Agung, 2022)
Abstract: The Pentecostal school has a distinctive and unique methodology or interpretation in understanding the Bible in a certain way, especially the teaching of the Holy Spirit in the book of Acts. This article is intended to describe the historical-theological character of the pneumatology of the Pentecostal school, especially in the book of Acts. Through literature review, the author describes three basic methodological problems, namely: first, the genre and theological unity of the Gospel of Luke-Acts; second, the theological character of Luke's historiography; and third, Luke's independence as a theologian. Based on this methodology, it can be concluded that Luke has a theology of the Holy Spirit which is more charismatic, not soteriological. Keywords: Acts of the Apostles, historical-theological character, Pentecostal, pneumatology. Abstrak: Aliran Pentakostal memiliki metodologi atau interpretasi yang khas dan unik dalam memahami Alkitab dengan cara tertentu, terkhusus pengajaran tentang Roh Kudus di kitab Kisah Para Rasul. Artikel ini dimaksudkan untuk mendeskripsikan karakter historis-teologis aliran Pentakostal mengenai pneumatologi, khususnya pada kitab Kisah Para Rasul. Melalui kajian pustaka, penulis menguraikan tiga masalah metodologi yang mendasar, yaitu: pertama, kesatuan genre dan teologis Injil Lukas-Kisah Para Rasul; kedua, karakter teologis dari historiografi Lukas; dan ketiga, independensi Lukas sebagai seorang teolog. Berdasarkan metodologi tersebut, diperoleh simpulan bahwa Lukas memiliki sebuah teologi Roh Kudus yang lebih bersifat karismatik, bukan soteriologis. Kata-kata kunci: Kisah Para Rasul, karakter historis-teologis, Pentakostal, pneumatologi.